HORSES AND GESTALT COACHING: A PROMISING COMBINATION FOR LIFE SKILLS LEARNING - Grēve, Māra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Life skills play an important role in developing adaptive behaviours that are necessary to improve one’s quality of life. An individual with a broad range of life skills is more resilient than one with fewer skills. They can better withstand the challenges of constant change, successfully coping with stress and creating a fulfilling life. The aim of this research is to theoretically substantiate the possible benefits of equine-partnered gestalt coaching in life skills learning. Both Gestalt coaching and horses – specifically in context of different methods incorporated in equine assisted activities – are mentioned as they relate to the improvement of various aspects of quality of life based in life skills learning.